Case report: Paravalvular regurgitation post transcatheter aortic valve replacement: When in doubt choose cardiac magnetic resonance - Hadley, Michael B.; Prandi, Francesca Romana; Barillà, Francesco; Sharma, Samin; Kini, Annapoorna; Lerakis, Stamatios (Frontiers in Cardiovascular Medicine, 2022)
Paravalvular leak (PVL) is a common complication following transcatheter aortic valve replacement (TAVR). Significant PVL is associated with adverse prognosis, but may be challenging to assess accurately. We report the case of an 81-year-old man with shortness of breath 5 months post TAVR. Echocardiography classified PVL as either moderate or severe depending on the parameter utilized, while angiography found only mild PVL. Cardiac magnetic resonance allowed an exact quantification of regurgitant flow volume, classified as clinically and hemodynamically significant. This case highlights the role of multimodality imaging assessment including cardiac magnetic resonance for a more accurate assessment of PVL severity, especially when other imaging modalities show discordant results.